Modelling the Impact of Tillage on Water Quality for Sustainable Agricultural Development in a Savanna Ecological Zone, Kwara State, Nigeria - Agaja, Toluwalope Mubo; Ajibade, Lanre Tajudeen; Agaja, Micheal Olufemi (Journal of Environmental Geography, 2021)
The aim of the study was to examine the effects of tillage methods on surface runoff and model the pattern and processes of surface water pollution associated with tillage methods using Soil Water Assessment Tool (SWAT). This model was designed to predict the impact of land management practices on water, sediment, and varying tillage types in watersheds over two planting seasons. Traditional heap (T), Plough/Harrow (PH), Plough/Harrow/Ridge (PHR) and No-tillage (NT) methods commonly used in the study area were applied to experimental plots at Unilorin Teaching and Research Farm and National Center for Agricultural Mechanization, Idofian (Nigeria). Using Randomized Complete Block Design (RCBD), each treatment had three replicates making 12 experimental plots at each location for the 2015 and 2016 planting season. Nine biophysical parameters were purposively selected, examined and modelled. The study revealed that four of nine biophysical factors (sediment yield: 10.54 t/ha; groundwater discharge: 174.45 mm; organic nitrogen: 62.62 kg/ha, and nitrogen in surface runoff: 5.15 kg/ha) were higher for traditional heaps, while three parameters (surface runoff: 374.42 mm; evapotranspiration: 752.78 mm, and soil loss: 1.05 kg/ha) were higher under plough/harrow and plough/harrow/ridge cultivation practices. The study concluded that tillage methods have impact on water quality. However, plough/harrow has comparatively more favorable effect on the contribution to surface runoff. It is therefore recommended that this type of tillage should be adopted to reduce water pollution and for sustainable environment.